Release Pattern of Nitrogen and Potassium from Controlled Release Fertilizer (CRF) in the Soil - Suwardi Suwardi; Dyah Tjahyandari Suryaningtyas; Hens Saputra; Mochamad Rosjidi; Anwar Mustafa; Abdul Ghofar (JOURNAL OF TROPICAL SOILS, 2023)
Nitrogen (N) and potassium (K) are macronutrients that plants need for better growth and yield. However, they are readily lost from the soil through volatilization, denitrification, and leaching, aside from being absorbed by plant roots. Thus, a Controlled Release Fertilizer (CRF) may be formulated and applied to maximize the beneficial effects of N and K fertilization. This study aimed to describe the release pattern of ammonium nitrogen (NH4 -N), nitrate nitrogen (NO3 -N), and K from CRF through the laboratory incubation method. Two types of CRF - CRF A (16-16-16) and CRF B (30-6-8), with a non-CRF (Mutiara NPK16-16-16) as Control – were used. Each fertilizer was tested at 600 and 1200 kg ha-1 doses. The results showed that the NH4 -N release was very high at 40 – 60% but declined to almost 0% after 14 weeks. The NO3 -N release rate was 17 – 40% during the first week, followed by a steady increase to nearly 100% by the 14th incubation week. Potassium release ranged from 20% to 30% in the first week, then rose to 30 – 70% at Week 14. Overall, CRF (30-6-8) at a dose of 1200 kg ha-1 showed the slowest rate of nitrogen release.